2020
DOI: 10.2217/bmm-2020-0317
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hematological Parameters in Covid-19 Patients in the Emergency Room

Abstract: Aim: In this study, the roles of biomarkers from a peripheral blood sample in the diagnosis of Coronavirus Disease of 2019 (COVID-19) patients who have visited the emergency room have been evaluated. Materials & methods: Peripheral blood parameters, systemic inflammatory index (SII), neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio were compared in patients with and without confirmed COVID-19 infection. Results: Comparisons made according to real-time PCR test results revealed that while no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
126
9
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(155 citation statements)
references
References 21 publications
17
126
9
3
Order By: Relevance
“…However, it was 1.8 times higher among survivors in our study. This is in stark contrast with the trend observed in a study conducted by Usul et al, wherein NLR was was found to be significantly high in critically ill COVID-19 patients compared to the control population [12]. LMR was also higher in survivors but the association was not statistically significant.…”
Section: Discussioncontrasting
confidence: 93%
“…However, it was 1.8 times higher among survivors in our study. This is in stark contrast with the trend observed in a study conducted by Usul et al, wherein NLR was was found to be significantly high in critically ill COVID-19 patients compared to the control population [12]. LMR was also higher in survivors but the association was not statistically significant.…”
Section: Discussioncontrasting
confidence: 93%
“…TLC, ANC, ALC, NLR and Platelet counts among the survivors versus non survivors (p<0.05). Similar findings have been reported from a study conducted in Ankara Turkey [9]. Another study from Karachi Pakistan reported 364 Covid-19 patients, with 27.7% mortality.…”
Section: Discussionsupporting
confidence: 89%
“…Our finding is in contrast to the overall trend of decreasing platelet count with increasing disease severity, found in the studies from the US, China and Korea [31][32][33][34]. One study from Turkey showed that the platelet count was significantly low in COVID-19 PCR positive cases compared to PCR negative cases [35]. We also learnt that 31.7% (13/41) of the asymptomatic patients had thrombocytopenia at presentation.…”
Section: Discussioncontrasting
confidence: 95%